Biochar and compost amendment to enhance sweet corn growth / Nur Suraya Abdullah, Muhammad Arsyad Abdul Rahman and Noorshilawati Abdul Aziz - Abdullah, Nur Suraya; Abdul Rahman, Muhammad Arsyad; Abdul Aziz, Noorshilawati (Universiti Teknologi MARA, Sabah, 2022)
Planting in polybags is a common solution to the issue of limited land for agricultural activity in urban areas. The proper use of planting medium and amendment with beneficial organic compounds such as biochar and compost could provide high yield in return. The present study aimed to evaluate the effects of biochar and compost application in the medium for corn grown in polybags. Five treatments comprised of T0 (soil) as control, T1 (soil and compost at ratio 1:1), T2 (soil and biochar at ratio 1:1), T3 (soil, compost, and biochar at ratio 1:1:0.5), and T4 (soil, compost, and biochar at ratio 1:2:2) were prepared. The experiment was arranged in a randomized complete block design (RCBD) with four replications. The results indicated that the highest corn performance was recorded in T2. The mean values were significantly different in some growth parameters such as stem diameter (2.82 cm), fruit weight (307.25 cm), fruit diameter (5.71 cm), and plant fresh weight (324.00 g) as compared to control and other treatments. The results also found that biochar is more efficient for corn grown in polybags than compost. However, soil amended with a high amount of biochar and compost has reduced corn growth. The study provides beneficial information and contributions to the existing literature on the optimization of suitable medium for promoting corn growth in polybags. Using biochar and compost can reduce dependency on extensively used inorganic fertilizer, which is harmful to the environment.